Preservice teachers’ perceptions of gender equity issues in the mathematics classroom - Mewborn, Denise S.; Gober, Deborah A. (NOMAD Nordic Studies in Mathematics Education, 1998)
The purpose of the study was to identify preservice teachers’ perspectives on gender equity and to explore how they process the information they receive about gender issues. Data were collected through written surveys administered to 225 preservice and inservice teachers enrolled in mathematics and science education (methods) courses at the university. Data were analyzed using Paine’s (1990) categories of orientations to diversity: individual difference, categorical difference, contextual difference, and pedagogical difference. The study suggests that most preservice teachers have an individual difference view of gender equity in which they strive to treat all students the same to avoid discrimination. Some students hold a categorical view of gender equity in which they strive to overcome stereotypes about boys and girls. A small number of students actively denied that gender issues have any relevance to education.